Success Factors for an E-Government Strategy: Austrian Experiences, Indonesian Challenges - BEHRENS, CHRISTOPH (Jurnal Studi Pemerintahan, 2012)
Focus of this paper are success factors for the implementation of an E-Government strategy. Whileconcepts for a sophisticated strategy process in Public Sector are delivered on a regular basis, the gapbetween ambitious planning and its implementation seems to get wider. Authors seek to define whatmakes a â€œgood strategyâ€ in order to enhance management capacity. Meanwhile some scholars fromPolitical Science see limitation of Governments on announcements which are not followed up bysufficient action rather as systematic problems, challenging concept and rules of liberal westerndemocracy, or owed to growing complexity of Governance under the conditions of globalization. Incontext of the introduction of New Public Management and its perception of citizens as customers andon the basis of new available technical options in Information Society, a key Governance reform projectin European and other Countries over the last fifteen years has been the introduction of E-Government.European market leader in this field is Austria. The author reviews concept and implementationexperiences of the Austrian E-Government strategy, analyzes key success factors and opens adiscussion, under which conditions a successful implementation of E-Government can take place inIndonesia.